2013
DOI: 10.1155/2013/245476
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Efficiency of Positive Airway Pressure Treatment

Abstract: Objectives. The aim of this study was to evaluate the clinical efficiency and compliance of positive airway pressure (PAP) treatment. Materials and Methods. This study was conducted on moderate-severe obstructive sleep apnea syndrome (OSAS) patients who admitted to Ankara Numune Hospital Sleep Center between 2008 and 2012. Seventy-five patients with moderate-severe OSAS who were using PAP treatment regularly were enrolled in the study. Patient's usage data, Epworth sleepiness scale (ESS) scores, and the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Such improvement could only be ascribed to the reduction of nocturnal urine production because there was no improvement in other variables based on the frequency volume chart. There have been several studies about night‐time frequency in patient with OSAS . However, few studies have investigated the impact of CPAP treatment on nocturnal urine production and related QOL and biological findings .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such improvement could only be ascribed to the reduction of nocturnal urine production because there was no improvement in other variables based on the frequency volume chart. There have been several studies about night‐time frequency in patient with OSAS . However, few studies have investigated the impact of CPAP treatment on nocturnal urine production and related QOL and biological findings .…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies about night-time frequency in patient with OSAS. 18,19 However, few studies have investigated the impact of CPAP treatment on nocturnal urine production and related QOL and biological findings. 13 In addition, the problem of treatment compliance is frequently encountered in patients with OSAS.…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that positive airway pressure treatment significantly lessens the symptoms of OSAHS and related diseases; it is a gold standard therapy for moderate and severe OSAHS 9 …”
Section: Introductionmentioning
confidence: 99%
“…8 It has been revealed that positive airway pressure treatment significantly lessens the symptoms of OSAHS and related diseases; it is a gold standard therapy for moderate and severe OSAHS. 9 The present study aimed to explore the significance of the TNF-α/IL-10 ratio and the effect of continuous positive airway pressure (CPAP) in patients with different degrees of OSAHS severity.…”
Section: Introductionmentioning
confidence: 99%
“…Positive airway pressure is an effective method for treating patients with moderate and severe OSA [104]. The gold standard treatment for OSA is nasal continuous positive air pressure, which is correlated with improving sexual functioning and improving quality of life [68].…”
Section: Non-invasive Treatmentmentioning
confidence: 99%